Hadith Studies in Malaysia: A Meta-Analysis Approach - Ahmad, Khalilullah Amin; Asni, Fathullah; Abdul Hamid, Solahuddin; Abdul Rahman, Mohd. Nizho (Human Resource Management Academic Research Society, 2021)
Hadith studies have been going on since the times of the Prophet Muhammad (PBUH) with various methods. The teaching and learning (T&L) of hadith is an issue that researchers often study to enhance the level and quality of T&L itself. This is because there is the fact that the hadith lecturers are not creative in teaching, lack pedagogical skills and do not apply the latest innovative methods in the process of T&L. This meta-analysis was conducted to explore previous studies on the science of hadith studies in Malaysia from 2010 to 2021. Although there are many studies on hadith studies, there are still few studies in Malaysia. Based on the search, only seven studies are published on the science of hadith studies in Malaysia. The analysis conducted for these seven studies found certain elements in explaining the science of hadith studies in Malaysia. These studies also found that science of hadith studies in Higher Educational Institutions involved. In addition, this study also focused on the main findings of each study conducted. This study also examines the methodology of the study used. The findings of this study are intended to help future research in the science of hadith studies in Malaysia. In addition, this analysis also suggests some ideas for further research